Life Cycle Assessment for Fiber-Reinforced Polymer (FRP)nComposites Used in Concrete Beams: A State-of-the-Art Review - Ibrahim, Mohamed; Ebead, Usama; Al-Ansari, Mohammed (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Fiber-reinforced polymer (FRP) composites have become popularly utilized in structural engineering applications. The common use of the FRP composites is related to their economic benefits that can be observed right away or in a long-time period. With increasing concern about global warming and the shortage of natural resources, it is essential to study the environmental implications of the use of FRP composites. Life cycle assessment (LCA) is one of the most common techniques that can be used to take the environmental impact of the FRP into consideration. This paper presents a literature review about the LCA of FRP composites in concrete beams. The LCA results reported in the literature confirmed the use of FRP composites for reinforcing the RC beams instead of conventional steel rebars or that the strengthening of RC beams instead of demolishing and reconstruction is a more environment-friendly approach.